Growth and nutrients uptake of rice at early seedling stage as inoculated with Bacillus spp. - Shultana, Rakiba; Zuan, Ali Tan Kee; Othman, Radziah; Yusop, Mohd. Rafii (Plant Archives, 2019)
Utilization of plant growth promoting rhizo-bacteria (PGPR) potentially elevates crop productivity. Concurrently, our study was focused on isolating efficient PGPR strains from the rhizosphere of rice plants. This in order to assess its properties under both laboratory and glass house conditions accordingly. Five (5) bacterial isolates were screened out based on sets of qualitative tests. Among the bacterial isolates, UPMRB9 were selected due to higher production of plant growth promoting traits:- (1) nitrogen fixation, (2) phosphate and potassium solubilization, (3) indole-3 acetic acid production as well, (4) siderophore and hydrolyzing enzyme production. The isolates were later identified based on 16S rRNA sequence by which known to be Bacillus tequilensis. Subsequently, this potential isolates were inoculated to rice seedlings under control environment (glasshouse conditions). The results amply that seedling biomass was 38.2% (BRR1 dhan67), 38.5% (Putra-1) and 33.9% (MR297) higher in compare to uninoculated control. Similar goes for seedling height at 22.5%, 20.2% and 20.0% higher whilst total chlorophyll content was 22.5%, 20.2%, 20.0% higher respectively. The relative increase of nitrogen for the rice variety BRRI dhan67, Putra-1 and MR297 were 34.38%, 99.65% and 52.22% accordingly; phosphorous was 442.7%, 104.9%, 140.7% accordingly and potassium was 41.5%, 45.8%, 153.7% accordingly. Therefore, the isolates of UPMRB9 could be considered as a potential bio-fertilizer source; yet further evaluations are necessary particularly on its performances under field environment.